Precalculated arrays-based algorithms for the calculation of the Riemann zeta-function - Kuzma, Lukas; Belovas, Igoris; Sabaliauskas, Martynas (Vilnius University Open Series, 2022)
In this paper, we continue the study of efficient algorithms for the computation of the Riemann zeta function on the complex plane. We introduce two precalculated arrays-based modifications of MB-method. We perform numerical experiments with these algorithms using Zetafast as a benchmark and apply the algorithms for the visualizations of fractal structures associated with the Riemann zeta function.